Clerodane diterpenoids with anti-inflammatory activity from the tuberous root of Paratinospora sagittata (Oliv.) Wei Wang - Li, Hailin; Liu, Jing; Fang, Chuhong; Ning, Shanglei (Frontiers in Pharmacology, 2025)
Seven novel clerodane diterpenoids, designated tinotanoids I–O (1−7), were isolated from the tuberous roots of Paratinospora sagittata (Oliv.) Wei Wang [syn.: Tinospora sagittata var. yunnanensis (S.Y.Hu) H.S.Lo; Menispermaceae]. The structural elucidation of these new metabolites, including their absolute configurations, was achieved through advanced spectroscopic methods such as mass spectrometry (MS), nuclear magnetic resonance (NMR), electronic circular dichroism (ECD), and X-ray crystallography. Evaluation of their anti-inflammatory activity revealed that metabolites 3 and 4 exhibited potent inhibition of nitric oxide (NO) production in lipopolysaccharide (LPS)-activated RAW264.7 macrophages, with IC50 values of 12.5 ± 0.5 and 16.4 ± 0.7 μM, respectively, which are better than those of the positive controls, quercetin and dexamethasone. Additionally, metabolites 3 and 4 effectively inhibited the pro-inflammatory cytokines TNF-α and IL-6 in a dose-dependent manner.